ERS-1/JERS-1 SAR ニヨル ナンキョク ノ ヒョウガ ヒョウショウ ケンキュウ ワークショップ ホウコク - 平沢, 尚彦; ヒラサワ, ナオヒコ; 高橋, 晃; タカハシ, アキラ; 渡辺, 興亜; ワタナベ, オキツグ; 佐藤, 夏雄; サトウ, ナツオ; Hirasawa, Naohiko; Takahashi, Akira; Watanabe, Okitsugu; Sato, Natsuo (1996)
P(論文) 本研究小集会の目的はSARデータを使った南極氷床・氷河に関する最近の研究成果, 及び今後の研究計画について議論することである。本会は1996年2月6日, 極地研究所講義室において行われ, 出席者は約30名であった。SAR画像に見られる様々な模様にについての紹介, 飛行機観測や可視画像との比較, 現地氷状観測との比較, インターフェロメトリの今後の課題などが議論された。 The main purpose of the workshop is to discuss recent results of Antarctic research using SAR data. It was held on February 6,1996 at the National Institute of Polar Research (NIPR), the number of participants being about 30. The contents of the workshop are demonstration of various SAR images, comparison with pictures from an airplane and visible images, comparison with observational data on ice conditions and demonstration of problems in interferometry. departmental bulletin paper